Answer:
we conclude that:
[tex]\frac{6}{6^{\frac{1}{4}}}=6^{\frac{3}{4}}[/tex]
Step-by-step explanation:
Given
The expression is
To determine
Simplify the expression
Simplifying the expression
[tex]\frac{6}{6^{\frac{1}{4}}}[/tex]
Apply the exponent rule: [tex]\frac{x^a}{x^b}=x^{a-b}[/tex]
[tex]\frac{6}{6^{\frac{1}{4}}}=6^{1-\frac{1}{4}}[/tex]
Subtract the numbers: [tex]1-\frac{1}{4}=\frac{3}{4}[/tex]
[tex]=6^{\frac{3}{4}}[/tex]
Therefore, we conclude that:
[tex]\frac{6}{6^{\frac{1}{4}}}=6^{\frac{3}{4}}[/tex]